That Chinese "juggernaut": Should Europe really worry about its trade deficit with China? - Andreas Freytag (European Centre for International Political Economy (ECIPE), 2008)
China's exchange-rate policy has been under attack in the last years, especially in the United States. Now the critique of Beijing's policy is coming from Europe as well, and Chinese authorities are accused of boosting its own export, at others expense, by keeping its currency below its real value. At the centre of the European criticism has been the link between China's allegedly undervalued currency European Union's soaring bilateral trade deficit with China. This Policy Brief discusses EU-China trade relations in the context of China's exchange-rate policy. Especially it scrutinizes the assumptions underlying the link between China's exchange-rate policy and Europe's rising bilateral deficit. It finds this link tenuous, and argues that a bilateral deficit cannot prima facie be viewed as a problem when the overall current account of Europe largely is in balance.
Keywords: 330; Wechselkurspolitik; Außenhandel; Handelsbilanz; EU-Staaten; China